(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
When molybdenum is processed by powder metallurgy, insoluble molybdenum compounds arise, which form specs on the surface of nickel boats (Ni - 63%, Mo - 27% alloy). It is necessary to search for an effective technology for cleaning nickel boats from molybdenum cake, ensuring their repeated use and return to the production cycle of metal bound in the cake